Greater variation in affect is associated with lower fasting plasma glucose - Sunjai Gupta; Robert Anderson; Richard IG Holt (Heliyon, 2016)
Background: Depression and bipolar illness are associated with a 2–3 fold increase in the prevalence of diabetes. However, it is unknown whether variation in mood affects glucose metabolism. The aim of this study was to assess whether changes in affect were related to fasting plasma glucose and glycated haemoglobin. Methods: 379 men and 441 women who took part in the 2003 Health Survey for England and had valid data for GHQ12 and fasting blood glucose were included. Mood variability was assessed by the General Health Questionnaire 12 (GHQ12). Fasting plasma glucose and glycated haemoglobin (HbA1c) were measured by standard laboratory methodology and their relationship to variability assessed using linear regression. Results: There was a significant inverse relationship between fasting blood glucose, but not HbA1c, and variability score (R2 = 0.327, p = 0.02) after adjusting for sociodemographic factors, anthropometric measurements, lifestyle, and use of medication. Conclusion: This study has shown an inverse association between changes in affect and fasting plasma glucose. This unexpected finding suggests that the association between affect and glucose is more complex than previously thought. Fasting blood glucose may reflect the operation of homeostatic mechanisms that are disturbed in certain mental states and are associated, therefore, with altered risk of diabetes and related metabolic conditions. This may have implications for the management of those with such conditions and with mental disorders.